SHARIA FINANCIAL LITERACY FOR TEACHERS IN DARUL AMAN DISTRICT, ACEH TIMUR REGENCY - Ichsan Ichsan (LPPM, 2021)
This study aims to determine the Islamic financial literacy among teachers in Darul Aman sub-district, East Aceh Regency. It uses primary data obtained by distributing questionnaires to 80 respondents who were selected using Simple Random Sampling. The data analysis method used is simple linear regression. The data analysis method used is simple linear regression. The results partially show that Islamic financial literacy has a positive and significant effect on teachers in Darul Aman sub-district, East Aceh Regency. The results of the interview concludes that the knowledge of teachers in Darul Aman sub-district, East Aceh Regency on Islamic financial institutions is very good. Although they do not fully understand, they can already understand how the system is going on in Islamic financial institutions and conventional financial institutions, especially bank financial institutions